Some New Aspects of Genetic Variability in Patients with Cutaneous T-Cell Lymphoma - Vašků, Vladimír; Máchal, Jan; Zlámal, Filip; Vašků, Anna (Genes, 2022)
AIM: Cutaneous T-cell lymphoma (CTCL) is a group of T-cell malignancies that develop in the skin. Though studied intensively, the etiology and pathogenesis of CTCL remain elusive. This study evaluated the survival of CTCL patients in the 1st Department of Dermatovenereology of St. Anne's University Hospital Brno. It included analysis of 19 polymorphic gene variants based on their expected involvement in CTCL severity. MATERIAL AND METHODS: 75 patients with CTCL, evaluated and treated at the 1st Department of Dermatovenereology of St. Anne´s University Hospital Brno, Faculty of Medicine, Masaryk University, were recruited for the study over the last 28 years (44 men and 31 women, average age 58 years, range 20-82 years). All patients were genotyped for 19 chosen gene polymorphisms by the conventional PCR method with restriction analysis. A multivariate Cox regression model was calculated to reveal genetic polymorphisms and other risk factors for survival. RESULTS: The model identified MDR Ex21 2677 (rs2032582) as a significant genetic factor influencing the survival of the patients, with the T-allele playing a protective role. A multivariate stepwise Cox regression model confirmed the following as significant independent risk factors for overall survival: increased age at admission, clinical staging of the tumor, and male sex. CONCLUSION: We showed that the TT genotype at position 2677 of the MDR1 gene exhibited statistically significant longer survival in CTCL patients. As such, the TT genotype of MDR1 confers a significant advantage for the CTCL patients who respond to treatment.
Keywords: senioři; Lymphoma, T-Cell, Cutaneous; senioři nad 80 let; genotyp; skin T-cell lymphoma; Skin Neoplasms; Genotype; Middle Aged; polymorphism-MDR1; mužské pohlaví; Adult; mladý dospělý; polymorfismus genetický; Aged, 80 and over; Polymorphism, Genetic; mycosis fungoides; Young Adult; ženské pohlaví; Humans; nádory kůže; lidé středního věku; rizikové faktory; CTCL; dospělí; Female; kožní T-buněčný lymfom; Aged; Risk Factors; lidé; Male